Controlled Electrochemical Growth of Spinel NiCo2S4 Nanosheets on Nickel Foam for High Performance Supercapacitor Applications. (2018) - Sahoo, Surjit; Kumar Naik, Kusha; Sekhar Rout, Chandra
Abstract: Spinel metal oxides/sulfides possess higher reversible capacity, better electronic conductivity and have been investigated for high performance electrode materials for supercapacitors. Herein, we report a facile, low-cost and one-step electrodeposition approach for the synthesis of thin film NiCo2 S4 (NCS) nanosheet arrays on Ni foam substrate. The elemental composition and morphology of the materials are characterized by energy dispersive x-ray analysis and field-emission scanning electron microscopy. The supercapacitor performance of the NCS nanosheets are studied in three electrode configuration in 2M KOH electrolyte. The as-prepared binder free electrode showed a high specific capacitance of 1500 F/g at 3 A/g with excellent cycling stability even after 1000 charge/discharge cycles. Obtained energy density and power density of the NCS nanosheets are 50.58 Wh/Kg and 12.978 Kw/Kg respectively. The superior electrochemical performances are mainly attributed to its nanosheet like structure which provides large reaction surface area, fast ion and electron transfer rate.